AB0664 Frequency of hand osteoarthritis in patients with primary sjogren syndrome: Is there a relationship between two diseases?. (23rd January 2014) - Aksoy, A.; Solmaz, D.; Akar, S.; Gunduz, O.; Birlik, M.; Sari, I.; Ozaksoy, D.; Akkoc, N.; Onen, F.
Abstract : Background: The most common extra glandular finding of primary Sjogren's syndrome (SjS) is joint involvement. The distribution of arthritisin SjSis similarto that of rheumatoid arthritis (RA), primarily affecting the small joint of the hands but it has a milder course than RA. In the Framingham Osteoarthritis Study, prevalences of hand OA, erosive OA and symptomatic OA in women were estimated to be 44.2%, 9.9% and 15.9%, respectively. The prevalence of symptomatic hand OA in women aged >40 years was found to be 8.4% in Ankara, Turkey. There is very limited data on the relationship between SjS and hand OA. Objectives: To investigate the prevalence of hand OA in patients with primary SjS. Methods: The patients with primary SjS followed up in a university hospital were called by telephone and invited to participate to the study. We obtained a detailed medical history and performed full physical examination in patients who agreed to take part in the study. The demographic, clinical and laboratory data were recorded ona standardized form. Standard hand/wrist X-rays were ordered in all patients. They were read by an experienced rheumatologist and classified according to the Kellgren- Lawrence (KL) classification system. At joint level, radiographic hand OA was defined as KL grade ≥2, erosive OA as KL grade ≥2 plus central erosion and symptomatic hand OA as KL grade ≥2 plus pain/aching/stiffness. The definition of"erosive OA" was made according to the EULAR evidence-based recommendations in 2009. At subject level, participants with ≥1 affected joint(s) according to the definitions above were classified as cases. Results: We included 119 patients (115 female; 4 male) with primary SjS fulfilling the American-European classification criteria for primary SjS in this study. The mean age was 51.6 years. Initial symptoms were as follow: arthralgia (62.3%), dry eye (19.3%) and dry mouth (14.9%). Anti-nuclear antibody (ANA) was found to be positive in 72 patients (66.2%), rheumatoid factor (RF) in 31 patients (32%) and anti-CCP antibody in 3 patients (5.4%). The hand/wrist X-rays were obtained in 114 patients (110 female; 4 male). Among them, 62 patients (54.5%) had radiographic hand OA, 44 (38.6%) symptomatic hand OA and 23 (20.2%) erosive hand OA. The prevalence of radiographic, symptomatic and erosive hand OA in female patients was 55.5%, 39.1% and 20.9%, respectively. Joint involvement pattern similar to that in RA were reported in only two patients. The frequency of hand OA in patients was found to be positively correlated with increasing age (r: 0.513, p<0.001). Patients with erosive hand OA had significantly higher mean age than those without (p<0, 001). Cigarette smoking (p<0, 05) and ANA positivity (p<0, 001) were less common among patients with erosive hand OA than those without. No relationship was observed between the presence of erosive hand OA and inflammation markers or seropositivity for RF and anti-CCP. Conclusions: This study suggests that the frequency of hand OA may be higher in primary SjS patients than expected in the general population and confirms our clinical observations. However, it should be taken into consideration that methodological and geographic differences between the studies may affect the results. Disclosure of Interest: None Declared